PENAKSIR RASIO PROPORSI YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK BERSTRATA - Devri Maulana; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article we review three proportion ratio estimators for the population mean on stratified random sampling, i.e. traditional proportion ratio estimator, proportion ratio estimator using coefficient of regression, and proportion ratio estimator usingcoefficient of regression and curtosis as discussed by Singh and Audu [5]. The three estimators are biased estimators, then the mean square error of each estimator is determined. Furthermore, these mean square errors are compared to each other. This comparison shows that the proportion ratio estimator using coefficient of regression and curtosis more efficient than other estimators.